2019
DOI: 10.3390/agriculture9040085
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Dystocia and Perinatal Mortality in Extensively Kept Angus Suckler Cows in Germany

Abstract: Dystocia and perinatal mortality are major animal health, welfare and economic issues in beef suckler cow production. The objective of this study was to identify risk factors for dystocia and perinatal mortality and to analyze the relationships of both traits to external pelvic parameters in extensively kept beef suckler cows. Calving ease and calf survival were recorded for 785 births on five Angus cattle farms in Germany. The prevalence of dystocia and perinatal mortality was 3.4% and 4.3%, respectively. A h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…Birth weight was considered a very good economic indicator in the beef cattle industry [ 5 ] as it was positively associated with post-weaning gain [ 6 ] and mature weight [ 7 ]. Contrariwise, calf birth weight was also identified to be a crucial factor for calving ease and directly associated with dystocia and perinatal mortality [ 8 , 9 ]. Therefore, determining the heritability estimates of birth weight in a cattle herd might boost economic productivity by improving growth traits and limiting the associated birth weight problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Birth weight was considered a very good economic indicator in the beef cattle industry [ 5 ] as it was positively associated with post-weaning gain [ 6 ] and mature weight [ 7 ]. Contrariwise, calf birth weight was also identified to be a crucial factor for calving ease and directly associated with dystocia and perinatal mortality [ 8 , 9 ]. Therefore, determining the heritability estimates of birth weight in a cattle herd might boost economic productivity by improving growth traits and limiting the associated birth weight problems.…”
Section: Discussionmentioning
confidence: 99%
“…This variable was considered by many researchers as a good economic indicator as it was positively associated with post-weaning daily weight gain [ 6 ] and matured weight [ 7 ]. Contrastingly, previous studies concluded that BW is a valuable predictor of dystocia (difficulty in giving birth) in cow, perinatal mortality in calves [ 8 , 9 ], and a prolonged calving interval [ 10 ]. Aside from BW, the selection of a heavier weaning weight (WW) was also reported to prolong the gestation length (GL) [ 10 ] and provide a favorable response in age at first calving (AFC) [ 11 ].…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, the CE rate increased as the PO advanced. The BW of calves and the PO are considered the most important factors affecting CE (Hohnholz et al., 2019). Decreasing CE for light calves in PP and MP may be attributed to the increased incidence of stillbirth (Salem & Amin, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Decreasing CE for light calves in PP and MP may be attributed to the increased incidence of stillbirth (Salem & Amin, 2017). Additionally, decreasing CE in PP for heavy calves compared with older dams may be due to disproportionate pelvic dimensions of the dam and calf size (Hohnholz et al., 2019). The increased BW in MP did not decrease the CE rate as traditionally happens in cattle because of anatomical differences between buffalo and cattle, buffalo having more capacious pelvis and larger area of ileum (Purohit et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The risks of dystocia [11] can be caused and increased by numerous factors-. Regardless of parity, calf's sex, weight, body size, pelvic and dam measurements, such metabolic disorders as hypocalcemia and seasonal effects, as well as an impact of environmental stress at the time of or just before parturition have been identified as risk factors [12][13][14][15]. Complicated and prolonged calving that requires a veterinary surgical intervention is dystocia.…”
Section: Introductionmentioning
confidence: 99%